Use of restriction endonucleases for mapping the allele for beta s-globin. - Wilson, J T (1982)
We have reported the direct analysis of the allele for beta 2-globin by using restriction endonuclease Dde I coupled with blot-hybridization analysis. In that report we predicted that a major use of our analysis could be for the prenatal diagnosis of sickle cell anemia. Here we present such an analysis. In addition, this report also describes the use of a new enzyme Mst II, which also distinguish the beta s allele from the normal beta-globin allele. Blot-hybridization analysis with restriction endonuclease Mst II shows the 5' end of the normal beta-globin gene to reside on a fragment of approximately 1.14 kilobases, whereas the 5' end of the beta s-globin gene resides on a fragment of approximately 1.34 kilobases. Because the fragment sizes generated by Mst II are significantly larger than those generated by Dde I, one can easily perform a prenatal diagnosis for sickle cell by standard blot hybridizations onto nitrocellulose filters.